Thermodynamic properties of non - isothermal plasma of ICF - Gabdullin, M. T.; Ramazanov, T. S.; Ismagambetova, T. N.; Moldabekov, Zh. A.; Otarbay, Zh. Y.; Mamatova, M. B. (21st International Symposium on Heavy Ion Inertial Fusion. Autonomous Organization of Education “Nazarbayev University”, 2016)
In this work dense non - ideal, non - isothermal plasma of ICF (inertial confinement fusion) was considered...
Keywords: thermodynamic properties; non - isothermal plasma; Research Subject Categories::NATURAL SCIENCES::Physics::Elementary particle physics